Wilfred Burchett interviewed by Hazel de Berg in the Hazel de Berg collection - Burchett, Wilfred, 1911-1983.; De Berg, Hazel, 1913-1984. (1970)
Burchett speaks of his experience in Germany in 1938; becoming a journalist; working as a war correspondent for the London "Daily Express"; his feelings regarding the A-bomb; the cold war; his stay in China (1951); the Indo-China problems (Vietnam); his journalistic involvement in the Vietnam war; the books he has written; his views for the future.
Also available online
Timed summary (5 p.) and transcript available (22 p.)
Keywords: Burchett, Wilfred, -- 1911-1983 -- Interviews; Authors, Australian -- Interviews; Journalists -- Australia -- Interviews; War correspondents -- Australia -- Interviews